RETRACTED: The use of artificial intelligence to diagnose the disease - Suprun Elena; Tynchenko Vadim; Khramkov Vladimir; Kovalev Georgy; Soloveva Tatiana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001